Pengaruh yoghurt dan soyghurt kayu manis (Cinnamomum burmannii) terhadap kadar glukosa darah, insulin serum, dan malondialdehyde tikus pra sindrom metabolik - Rustanti, Ninik; Nafsih, Vifin Zakiahtin; Avisha, Rosita Nur; Purwanti, Rachma; Nissa, Choirun; Wijayanti, Hartanti Sandi; Afifah, Diana Nur; Kurniawati, Dewi Marfu’ah (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Pre metabolic syndrome is characterized by two of five risk factors: central obesity, dyslipidemia, hypertension, and increased fasting blood glucose. Cinnamon yogurt and soygurt contain antioxidants and fiber which can improve insulin sensitivity and blood glucose homeostasis and prevent cell damage in pre-metabolic syndrome conditionsObjective: This study aimed to determine the effect of cinnamon yogurt and soygurt on fasting blood glucose (FBG), serum insulin, and malondialdehyde (MDA) levels in pre-metabolic syndrome rats.Method: This study was an experimental study with a pre and post-test control group design. The subjects were 15 male Sprague Dawley rats which were divided into 5 normal control mice (K) and 10 pre metabolic syndrome mice with a diet high in fat and fructose for group P1 (yogurt) and P2 (soygurt) each of 5 mice. The yogurt and soygurt were given as much as 3.4 ml / g BW for 28 days. FBG levels were measured by the GOD-PAP method, while serum insulin and MDA levels were by the ELISA method. Different tests before and after treatment using Paired t-test or Wilcoxon. The difference tests between groups using the One-Way ANOVA test or Kruskal Wallis.Results: There were no differences in FBG and MDA levels between groups after intervention (p> 0.05). The highest percentage reduction in FBG in the P2 (-11.59%), then P1 (-4.06%). The decrease in MDA levels in group P1 = 19.17%, and P2 = 15.44% lower than K = 24.43%. After the intervention, the insulin level in group P2 (0.46 ng / ml) was significantly higher than P1 (0.318 ng/ml), but both were not different from K (0.384 ng / ml).Conclusion: There was no significant effect on the administration of cinnamon yogurt and soygurt to FBG, serum insulin, and MDA levels.